Occupational Shifts in Private Industry in the Milwaukee Metro Area - (:unkn) unknown (My University, 2009)
Employment patterns of companies with 100 or more employees (and financial institutions with 50 or more workers) were examined for the four-county Milwaukee metro area using summaries of annual EEO-1 reports. The data help identify occupational shifts, progress toward a diversified labor force and challenges facing Milwaukee area employers and workers. The advantage of this data base is that it shows the actual (rather than estimated) numbers of workers employed in all larger private companies and also shows changes in employment by gender and race/ethnicity. Total employment in the mid-sized and larger private companies remained nearly flat even though significant occupational shifts were observed. Companies are reporting far fewer workers engaged in blue collar manual labor (as skilled craftsmen, semiskilled operatives, or unskilled laborers) and increases in workers employed as professionals (usually with a four-year college degree or more), managers, sales workers, technicians (usually with 2+ years of college or technical training), and office staff. The loss of jobs for semi-skilled operatives (down by 10,467 over the last decade) has been particularly pronounced.
Keywords: labor market information; economic recession